In-situ tem observation of pd catalyzed graphene growth by current-induced annealing - Yaakob, Yazid; Rosmi, Mohamad Saufi; Mohamed, Mohamad Azuwa; Sidik, Siti Munirah; Tanemura, Masaki (Universiti Putra Malaysia, 2024)
The use of Palladium (Pd) as a substrate for studying graphene growth presents a unique avenue of exploration. Pd is known as a" carbon sponge" with extensively studied carbon solubility and diffusivity. This study uses Pd as a catalyst for studying graphene growth, revealing a solid-phase reaction process in in-situ transmission electron microscopy (TEM). The study reveals significant structural changes in amorphous carbon nanofibers (CNF) catalyzed with Pd when electrical potential is applied through two-probe system. Notably, the gradual recrystallization and agglomeration of Pd particles, beginning in the middle segment of the CNF and advancing toward the end, were observed under high current flow ranging from 0.35 µA to 12 µA. This transformation, influenced by joule heating and significant thermal gradients, led to the crystallization of amorphous carbon, resulting in sp 2 hybridized carbon formation and the formation of graphene sheets starting from the Pd surface's tip. Structural deformation and the breaking of the graphene sheet were observed at higher current flow of 35.0 µA due to saturated current flow and induced Joule heating. The successful synthesis of graphene with approximately 350 nm between the cathode and anode, was achieved within the in-situ TEM environment. This in-situ TEM approach provides insights into carbon-Pd interactions and addresses a significant research gap by enabling the observation of graphene formation at the nanoscale.